Impact of Engagement in The Local Community on Consumer Satisfaction and Preferences: The Case of Two Neighborhood Shopping Centers in Saint-Petersburg, Russia - Oksana U. YULDASHEVA; Olga A. KONNIKOVA; Dmitry E. PIROGOV (Communications of International Proceedings, 2022)
The paper presents the results of empirical study devoted to the impact of engagement in the local community of a neighborhood shopping center on consumer satisfaction with the tenant mix and its preference over different categories of competitors (other neighborhood shopping centers, non-neighborhood shopping centers, purchases through e-commerce). The study was conducted in spring 2022 based on two neighborhood shopping centers in St. Petersburg, Russia. A sample of 228 respondents was formed on the basis of subscribers of certain communities in the Vkontakte social media. The results have showed that engaged and non-engaged consumers practically do not differ in terms of socio-demographic characteristics and the average bill of their purchases but differ greatly in the frequency of visits and the average time spent in the shopping center. Engaged consumers are more satisfied with the tenant mix of shopping center both in general and in certain categories of products. Engaged consumers are more likely than non-engaged to prefer shopping in the shopping center under study than shopping in another neighborhood or non-neighborhood shopping center (however there are no significant differences between engaged and non-engaged consumers in their preferences for online shopping). It was found out that engaged consumers respond to the survey questions in more detail, which makes them more useful for consumer research purposes. The information from the empirical study can be used to develop marketing strategies to engage the consumers in local communities and determine the content of these strategies, including the choice of specific engagement tools.
Keywords: neighborhood shopping center; engagement in the local community; tenant mix satisfaction